Акустичний вимірювач товщини предметів - Волошин, Д. Є.; Д’яченко, С. Ф.; Зубков, О. В. (ХНУРЕ, 2019)
Methods and devices for measuring thickness are analyzed. The impossibility of measuring the thickness of wood with standard gauges is shown. A method for measuring the thickness of the board or timber is proposed. Calculated technical parameters of the meter. The basic and structural schemes, the algorithm and the software have been developed. Created an experimental sample. Accuracy test performed.
Keywords: товщиномір; STM32; мікроконтролер; ультразвуковий датчик